The Establishment upside down: a year of change in Brazil - Duque, Debora; Smith, Amy Erica (Revista de Ciencia Política, 2019)
This was a year of dramatic changes in Brazilian politics, as the established parties and actors that had dominated Brazilian politics for two decades were humbled. The year began with the administration of the extremely unpopular, lame duck President Michel Temer, and ended awaiting the inauguration of far-rightist President Jair Bolsonaro on January 1st, 2019. In this article, we describe and analyze the major events of 2018 in Brazilian politics. From the perspective of legislative and executive productivity, the year was largely uneventful, as President Michel Temer had spent most of his political capital mustering the legislative votes needed to avoid prosecution for corruption. Yet transformations were afoot in parties and civil society. Three of the country’s most traditionally important parties – the PT, PMDB, and PSDB – were decimated, and the PT’s icon and standard-bearer Lula da Silva imprisoned. Meanwhile, the right and far-right grew in importance, and Jair Bolsonaro won the presidency with the sponsorship of the previously extremely small Social Liberal Party (PSL).